Method for evaluating performance of polyisocyanate curing agent solid product

By measuring the adsorbed water content of solid products on the surface of polyisocyanate curing agent, the problem of foaming of solid products at high temperatures is solved, and a fast and low-cost evaluation method is provided to ensure the normal use of the product under high temperature conditions.

CN119269313APending Publication Date: 2025-01-07WANHUA CHEM GRP CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310821674.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-06
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Polyisocyanate curing agent solid products absorb moisture during storage, resulting in foaming during high temperature melting. The existing evaluation methods are not enough to evaluate the performance of the product under solvent-free high temperature conditions, resulting in difficulty in judging the shelf life.

Method used

By measuring the content of adsorbed water on the surface of solid products, if the surface adsorbed water quality content per gram of solid products is not higher than 0.9%, it is considered to have good performance. Soaking tests are used for alcohols, ketones and other solvents to calculate the surface adsorbed water content. , ensure that the product is used normally when heated and melted at high temperature.

Benefits of technology

This method can quickly and at low cost to identify the availability of solid products under high temperature conditions, avoid losses from suppliers and downstream customers, and ensure the normal use of the products under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004323643580000091
    Figure BDA0004323643580000091
  • Figure BDA0004323643580000101
    Figure BDA0004323643580000101
  • Figure BDA0004323643580000102
    Figure BDA0004323643580000102
Patent Text Reader

Abstract

The invention discloses a method for evaluating the performance of a polyisocyanate curing agent solid product, whether the polyisocyanate curing agent solid product can be used or not is judged by measuring the content of adsorbed water in the polyisocyanate curing agent solid product, and when the mass content of the adsorbed water on the surface of each gram of the solid product is not higher than 0.9%, the performance of the polyisocyanate curing agent solid product is good; the method is simple in operation and high in accuracy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for evaluating the performance of a polyisocyanate curing agent solid product, and belongs to the field of polyurethane curing agents. Background Art

[0002] The preparation of polyisocyanate curing agent mainly adopts the trimerization reaction or alcohol modification reaction of diisocyanate monomer under the action of catalyst. After reaching the expected conversion rate, vacuum distillation or thin film evaporation is used to remove the unreacted monomer to obtain the polyisocyanate curing agent product, such as patents US4288586, US6093817, CN107827832, etc.

[0003] Some polyisocyanate curing agents are solid at room temperature. In order to facilitate downstream applications, they are prepared into solid products. Please refer to patents CN108299403A, CN212528342U, etc.

[0004] Solid products of polyisocyanate curing agents are inevitably exposed to air during actual storage, and different manufacturers have different degrees of product protection, and the environment in which the solid products are placed is also very different. Therefore, it is difficult to judge the shelf life of the product. For example, simple tests of conventional molecular weight distribution, NCO and other indicators did not find obvious abnormalities, but foaming will occur when melted at high temperature under solvent-free conditions, and the melting temperature will increase, which is not conducive to the use of downstream customers. In other words, the current evaluation method for solid polyurethane curing agent products is not sufficient to assess whether the solid products are qualified under solvent-free high-temperature conditions.

[0005] Therefore, how to evaluate the performance of polyisocyanate curing agent solid products quickly and at low cost is extremely important in the industry. Summary of the invention

[0006] In view of the shelf life problem of solid products in the actual storage process, the present invention provides a method for evaluating the performance of polyisocyanate curing agent solid products, which can quickly identify whether the solid product is usable under solvent-free and high-temperature conditions, and can avoid losses to suppliers and downstream customers at a low cost.

[0007] In the actual research process, the applicant surprisingly found that the solid product would absorb moisture during storage. This moisture did not undergo the conventional chemical reaction of forming urea with the isocyanate group, so the molecular weight distribution and NCO content of the solid product were not affected during the conventional dissolution test. However, when heated and melted under solvent-free conditions, the solid product could not be used normally.

[0008] To solve the above problems, the present invention provides the following technical solutions:

[0009] A method for evaluating the performance of a polyisocyanate curing agent solid product is disclosed. The method determines whether the polyisocyanate curing agent solid product is usable by measuring the content of surface adsorbed water on the solid product. When the mass content of surface adsorbed water per gram of the solid product is not higher than 0.9%, the polyisocyanate curing agent solid product is considered to have good performance and can continue to be used.

[0010] In the present invention, the method for determining the content of adsorbed water comprises the following steps:

[0011] a. Add the solid product to be tested into the solvent and soak it;

[0012] b. Using the same amount of solvent as a blank control;

[0013] c. Testing the water content of the solvent in which the solid product to be tested is immersed and the water content of the blank control solvent, and calculating the surface adsorbed water mass content of the solid product;

[0014] In the present invention, the solvent mainly includes alcohols, ketones, acids, aldehydes, preferably alcohols, more preferably methanol, ethanol, n-propanol, isopropanol, and most preferably anhydrous ethanol;

[0015] In the present invention, the soaking time is 1-60 min, preferably 5-30 min, and more preferably 5-10 min, and manual shaking or stirring is performed during the soaking process to accelerate the soaking.

[0016] In the present invention, the mass of the solid product to be tested can be 1-100 g, preferably 5-50 g, and more preferably 5-10 g; the mass of the solvent used is 3-4 times the mass of the solid product to be tested;

[0017] In the present invention, the calculation formula of the mass content of water adsorbed on the surface of the solid product is: (the mass content of water in the solvent in which the solid product to be tested is immersed - the mass content of water in the blank solvent) * the mass of the solvent / the mass of the solid product;

[0018] In the present invention, the determination of the content of surface adsorbed water is carried out under constant temperature and humidity conditions, preferably at a temperature of 15-40° C. and a humidity of 10%-60%;

[0019] In the present invention, the form of the solid product is not particularly limited, but a granular product is preferred. The shape of the granular product is preferably hemispherical, elliptical hemispherical, etc., with an average particle size of 0.5-3 cm, preferably 1-2 cm.

[0020] In the present invention, the Tg of the polyisocyanate curing agent is required to be not less than 35° C., such as 45° C., 55° C., 65° C., 75° C., preferably not less than 50° C., and more preferably 50-60° C. The Tg temperature range of the polyisocyanate curing agent prepared in the prior art is usually 30-80° C., but the inventors have found through experiments that the Tg of the molten polyisocyanate curing agent used in the granulation process needs to be controlled within a certain range. If the Tg is too low, it is difficult for the material to be completely cooled under normal conditions (room temperature 25-30° C.), which easily leads to solid adhesion and inability to effectively obtain a molded product.

[0021] In the present invention, the polyisocyanate curing agent is an existing product, and technicians can prepare it by any publicly available method or directly purchase it. For example, in some examples of the present invention, the preferred method is: preparing it by trimerization of diisocyanate monomers under the action of a catalyst or by reacting diisocyanate monomers with organic compounds containing active hydrogen, and preferably removing unreacted diisocyanate monomers after the reaction is completed.

[0022] In some examples, the diisocyanate is selected from one or more of aliphatic diisocyanates, alicyclic diisocyanates, and aromatic diisocyanates, preferably one or more of tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, xylene diisocyanate, cyclohexyl dimethylene diisocyanate, lysine diisocyanate, and toluene diisocyanate, more preferably one or more of toluene diisocyanate, isophorone diisocyanate, and cyclohexyl dimethylene diisocyanate.

[0023] In some examples, the catalyst is selected from one or more of organic ammonium or its weak acid salt, metal salt of alkyl carboxylic acid, preferably tetramethylammonium hydroxide, tetrabutylammonium hydroxide, tetraethylammonium hydroxide, benzyltrimethylammonium hydroxide, tetramethylammonium acetate, tetraethylammonium acetate, tetrabutylammonium acetate, dodecyltrimethylammonium octanoate, 2-hydroxy-N,N,N-trimethyl-1-propylammonium formate, 2-ethylhexanoic acid-N-(2-hydroxypropyl)-N,N,N-trimethylammonium salt, potassium acetate, potassium octanoate, 2-butyl lead hexanoate, more preferably one or more of 2-hydroxy-N,N,N-trimethyl-1-propylammonium formate, 2-ethylhexanoic acid-N-(2-hydroxypropyl)-N,N,N-trimethylammonium salt, tetramethylammonium hydroxide, tetrabutylammonium hydroxide, tetraethylammonium hydroxide, benzyltrimethylammonium hydroxide.

[0024] The amount of the catalyst used is 20-500ppm, preferably 50-250ppm, of the mass of the diisocyanate monomer; the catalyst can be added directly or prepared with an organic solvent to form a solution, for example, dissolved in n-butanol to form a solution with a concentration of 20wt%.

[0025] In some examples, the active hydrogen-containing organic compound is selected from a compound having one or more of -OH, -NH and -SH groups and an average functionality of at least 1.5, preferably a compound containing an -OH group and an average functionality of 2-3, more preferably one or more of diols (e.g., ethane-1,2-diol, propane-1,3-diol, propane-1,2-diol, butane-1,4-diol) with a molecular weight of 100-2500, triols (e.g., glycerol, trimethylolpropane) and tetraols (e.g., pentaerythritol), or one or more of polyaspartic acid esters, polythiols, polyhydroxy compounds, such as one or more of polyether polyols, polyester polyols, polyurethane polyols, polysiloxane polyols, polycarbonate polyols, polyether polyamines, polybutadiene polyols, polyacrylate polyols, polymethacrylate polyols, etc.

[0026] In some examples, the trimerization reaction temperature is 40-120°C, preferably 50-100°C; the reaction temperature of the reaction of the diisocyanate monomer with the active hydrogen-containing organic compound is 40-120°C, preferably 50-100°C;

[0027] When the conversion rate of the diisocyanate monomer reaches 20-70%, such as 30%, 40%, 50%, 60%, the trimerization preparation or the reaction of the diisocyanate monomer with the organic compound containing active hydrogen is terminated, and the conversion rate can be monitored by monitoring the NCO content of the reaction system;

[0028] Preferably, the trimerization reaction is terminated by adding an acidic substance to deactivate the catalyst;

[0029] The acidic substance is preferably one or more of hydrochloric acid, sulfuric acid, phosphoric acid, dibutyl phosphate, diisooctyl phosphate, and p-toluenesulfonic acid;

[0030] Wherein, the amount of the acidic substance added is preferably 1-10 times the molar amount of the catalyst, preferably 1.1-5 times;

[0031] Alternatively, the trimerization reaction may be terminated by thermal inactivation, with the temperature being kept at 130-150° C. for 20-60 min, such as at 130° C. for 30 min.

[0032] Preferably, the desired end point is achieved by controlling the molar ratio of the raw material diisocyanate to the organic compound containing active hydrogen through the reaction of the diisocyanate and the organic compound containing active hydrogen;

[0033] The molar ratio of diisocyanate to the organic compound containing active hydrogen is preferably 2-6:1.

[0034] In some examples, after the reaction is completed, the method for removing unreacted diisocyanate monomers is selected from any one of thin film evaporation, falling film evaporation, short path evaporation, and vacuum distillation. For example, by thin film evaporation, the separation temperature is 110-200°C and the pressure is 1-500PaG, and the monomer content of the obtained polyisocyanate product is less than 0.5wt%.

[0035] In the present invention, the polyisocyanate curing agent after the removal of unreacted monomers is maintained in a molten state and transported to a distributor of a steel belt granulation device to obtain the solid product of the present invention.

[0036] The method for evaluating the shelf life of a solid polyisocyanate curing agent product of the present invention can quickly identify product quality at low cost. Through the evaluation method of the present invention, the surface adsorbed water mass content of the solid product is controlled to be no higher than 0.9%, which can ensure that the solid product can be used normally during a high-temperature heating and melting process. The operation is simple and the accuracy is high. DETAILED DESCRIPTION

[0037] The method provided by the present invention will be further illustrated by the following examples, but the present invention is not limited thereto.

[0038] 1. The main raw materials used in the examples of the present invention are as follows. Other materials are common commercially available raw materials unless otherwise specified:

[0039] Toluene diisocyanate (TDI): Wanhua Chemical Group Co., Ltd.

[0040] Isophorone diisocyanate (IPDI): Wanhua Chemical Group Co., Ltd.

[0041] Tetrabutylammonium hydroxide: Sigma-Aldrich, 95%;

[0042] n-Butanol: Sigma-Aldrich, 98%;

[0043] Trimethylolpropane (TMP): Wanhua Chemical Group Co., Ltd.

[0044] Diethylene glycol (DEG): Sigma.

[0045] Anhydrous ethanol: Sigma

[0046] Propionic acid: Sigma

[0047] Acetaldehyde: Sigma

[0048] 2. The main test methods used in the present invention are:

[0049] 1) The NCO content test adopts the national standard GB / T 12009.4: the isocyanate group in the test sample is neutralized with an excess of 2 mol / L di-n-butylamine, and then back-titrated with 1 mol / L hydrochloric acid to obtain the NCO group content based on the total mass of the sample.

[0050] 2) Solvent water content test: based on Karl Fischer method (unit, %)

[0051] 3) Test method for surface adsorbed water mass content (A) Steps:

[0052] At room temperature (humidity 26%), take 10g of solid product and place it in a 250ml disposable plastic cup, then add 30g of anhydrous ethanol, then cover the mouth of the plastic cup with a glass watch glass, shake it by hand for 5 minutes to ensure that all the solid product is immersed, and then quickly test the water content of anhydrous ethanol.

[0053] Blank test: Use the same 250ml disposable plastic cup, add 30g of anhydrous ethanol, perform the same operation, and then test the water content of the anhydrous ethanol.

[0054] The mass content of water adsorbed on the surface of each gram of solid product = (the mass content of water in the anhydrous ethanol soaking the solid product to be tested - the mass content of water in the blank anhydrous ethanol) * 30 / 10

[0055] The test method for the mass content of surface adsorbed water (B) is the same as above, but the solvent is acetone.

[0056] The test method (C) for the mass content of surface adsorbed water is the same as above, but the solvent is propionic acid.

[0057] The test method for the mass content of surface adsorbed water (D) is the same as above, but the solvent is acetaldehyde.

[0058] 4) High-temperature melting observation: Take 250g of solid product and place it in a 500ml white-mouth glass bottle and seal it with a rubber stopper. Heat it in an oil bath at 140℃ and observe the internal melting phenomenon: normal phenomenon is a flowing liquid with no bubbles or few bubbles. Abnormal phenomenon is a large amount of white foam accompanied by the collapse of the stopper.

[0059] 3. Preparation of solid product of polyisocyanate curing agent a

[0060] Preparation of polyisocyanate curing agents based on isophorone diisocyanate (IPDI)

[0061] Preparation of catalyst solution: Tetrabutylammonium hydroxide was dissolved in n-butanol to prepare a solution with a concentration of 20 wt%.

[0062] Preparation of curing agent: 1000 kg of IPDI was placed in a reaction kettle, the reaction system was heated to 70° C., and then the catalyst solution prepared above (the catalyst amount was 150 ppm of the mass of IPDI) was added dropwise to the reaction system under stirring, and the reaction temperature was controlled between 70-80° C. to carry out polymerization reaction. When the conversion rate of IPDI was 60%, dibutyl phosphate in an amount equimolar to the catalyst was added to terminate the reaction to obtain a polymerization reaction liquid;

[0063] A thin film evaporator was used to evaporate and remove unreacted IPDI monomer in the polymerization reaction liquid at a temperature of 180°C and an absolute pressure of 50 Pa until its content was reduced to 0.34wt%. The molten material was then transported to a CF-6000 rotary steel belt granulation equipment at a temperature of 175°C for granulation to obtain polyisocyanate curing agent a.

[0064] Polyisocyanate curing agent a: Tg is 60°C.

[0065] 4. Preparation of solid product of polyisocyanate curing agent b

[0066] Preparation of polyisocyanate curing agent based on toluene diisocyanate (TDI)

[0067] 1000 kg of TDI was placed in a reactor in advance, and the materials in the reactor were heated to 90°C in an oil bath. A mixture of 66 kg of trimethylolpropane and 38 kg of diethylene glycol was continuously added within 60 minutes for reaction. The reaction was continued at 88°C with stirring for 3 hours to obtain a reaction liquid. Excess TDI monomer in the reaction liquid was removed by two-stage vacuum thin film distillation at 160°C and a pressure of 50 Pa to obtain a curing agent product with a TDI monomer content of 0.2 wt%. The product was then transported to a CF-6000 rotary steel belt granulation equipment maintained at a molten state of 150°C for granulation to obtain a solid product b.

[0068] Molten polyisocyanate curing agent b: Tg is 42°C.

[0069] Examples 1-6 and Comparative Examples 1-2

[0070] The solid curing agent product a was stored at room temperature for different periods to obtain corresponding samples, and the corresponding adsorbed water mass content test and the corresponding high-temperature melting experiment were carried out. At the same time, an evaluation method different from that of the present invention was used for evaluation. The results are shown in the following table.

[0071] Description: Product qualification control index: NCO content is 17.3±0.5%.

[0072] Comparative Example 3: Evaluation of different selected solvents

[0073] The surface adsorbed water mass content was tested by the same method as in Example 1 (method A), but the immersion solvent used was butyl acetate.

[0074] Table 1 Evaluation indexes of Examples 1-5 and Comparative Examples 1-3

[0075]

[0076]

[0077] Examples 7-11 and Comparative Examples 4-5

[0078] The curing agent product b was tested, and the test method for the surface adsorbed water mass content of Examples 7-9, Example 11, and Comparative Example 4 was selected as B, and the solvent was acetone.

[0079] The main difference between the surface adsorbed water mass content test method of Example 10 and Comparative Example 5 and that of Example 7 is that method C is selected and the solvent is propionic acid.

[0080] The qualified index of NCO content of curing agent product b is: 17.5±0.5%

[0081] Table 2 Evaluation indexes of examples and comparative examples

[0082]

[0083] Examples 12-13

[0084] The commercially available product T1890-100 was used for comparative testing. The initial NCO content was 17.3%. The surface adsorbed water mass content was tested using test method (D). The solvent was acetaldehyde.

[0085] Storage condition 1: 25℃, humidity 20%, storage for 6 months

[0086] Storage condition 2: 25℃, humidity 90%, storage for 6 months

[0087] Table 3 Evaluation indexes of Examples 12-13

[0088]

[0089] It can be seen from the above data that when the NCO content test is qualified, the mass content of adsorbed water in the solid product is actually increasing, and the high-temperature melting test process has been different. Therefore, the rapid evaluation method according to the present invention can quickly identify the high-temperature application of solid curing agent products.

Claims

1. A method for evaluating the performance of a polyisocyanate curing agent solid product, characterized in that: Whether the polyisocyanate curing agent solid product can be used is determined by measuring the surface adsorbed water content in the solid product. When the surface adsorbed water mass content per gram of solid product is not higher than 0.9%, the solid product of the polyisocyanate curing agent is considered to have good performance and can continue to be used.

2. The evaluation method according to claim 1, characterized in that: The method for determining the content of surface adsorbed water comprises the following steps: a. Add the solid product to be tested into the solvent and soak it; b. Using the same amount of solvent as a blank control; c. Test the water content of the solvent soaked with the solid product to be tested and the water content of the blank control solvent, and deduce the surface adsorbed water mass content of the solid product.

3. The evaluation method according to claim 2, characterized in that: The solvent mainly includes alcohols, ketones, acids, and aldehydes, preferably alcohols, more preferably methanol, ethanol, n-propanol, isopropanol, and most preferably anhydrous ethanol.

4. The evaluation method according to claim 2 or 3, characterized in that: The soaking time is 1-60 min, preferably 5-30 min, and more preferably 5-10 min. During the soaking process, the mixture may be manually shaken or stirred to accelerate the soaking.

5. The evaluation method according to any one of claims 2 to 4, characterized in that: The mass of the solvent used is 3-4 times the mass of the solid product to be tested.

6. The evaluation method according to any one of claims 1 to 5, characterized in that: The calculation formula for the mass content of water adsorbed by the solid product is: (the mass content of water in the solvent soaked with the solid product to be tested - the mass content of water in the blank solvent) * the mass of the solvent / the mass of the solid product.

7. The evaluation method according to any one of claims 1 to 6, characterized in that: The determination of the surface adsorbed water content is carried out under constant temperature and humidity conditions, preferably at a temperature of 15-35° C. and a humidity of 10%-60%.

8. The evaluation method according to any one of claims 1 to 7, characterized in that: The solid product is a granular product, the shape of the granular product is hemispherical or elliptical hemispherical, and the average particle size is 0.5-3 cm, preferably 1-2 cm.

9. The evaluation method according to any one of claims 1 to 8, characterized in that: The Tg of the polyisocyanate curing agent is not lower than 35°C, preferably not lower than 50°C, more preferably 50-60°C.

Citation Information

Patent Citations

  • TGIC (Triglycidyl Isocyanurate) production method based on fused steel belt granulation

    CN108299403A

  • Dust-free anti-sticking steel belt granulator

    CN212528342U

  • Process for the preparation of polyisocyanates containing isocyanurate groups

    US4288586A

  • Process for preparing a reduced-color isocyanurate-functional polyisocyanate prepared from 1-isocyanato-3,3,5-trimethyl-5-isocyanatomethylcyclohexane (IPDI)

    US6093817A